(3LgO GdfUjM hMX GdefjM ef eSGLdI GdeYQi aj NWHI GdaUjMs - (3GdcdGYj , SdjeGf Hf ehSi Hf SGde Hf MSGf GdMejQj, CHh GdQHjY,J (B634 (3g` s
(3ChdgG (B:s
(3CNHQfG GdTjN Gdabjg CHh GdQHjY bQGAI Ydjg SfI JSY hYTQjf hSJ eFI (B: (3QHfG Efc JYde eG fNai heG fYdf s
(3BNQgG (B:s
(3hbO UOYJ dce jMGdgG bHd GdSDGd , hcTaJ dce Yf hHGd CeQgG ai GdeBd , hSCQjOce Ef TGA Gddg HYjhHgG JHUjQkG s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfis
(3GdNWHI HYV edGeM GdNW GdeZQHis
(3HChdgG UhQI ELGRI ef GdeDda eDQNI SfI (B629 (3g` dQhGjgG Yfg CHj YHO Gddg GdYHOQis
(3hHBNQgG bQGAI CHh HcQ Hf YeQ Hf YHO Gddg He UGdM GdbQTi cJHgG HNWI SfI (B651 (3g`s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B136 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B399s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 s
Keywords: (3GddZIs